TIME OF MACHINES THAT CAN COMMUNICATE: THE AGE OF ARTIFICIAL INTELLIGENCE - CERECİ, Sedat (SSD Journal, 2025)
It is frequently discussed that the machines people produce behave like humans and replace humans. The first tools and machines that could do simple tasks made people’s lives easier, met their needs and contributed to the development of civilization. Civilization, which ensures that all human needs are met, has progressed with the development of tools and machines. When people first encountered mechanical tools, they most likely did not think that one day machines would be able to talk. However, approximately 4500 years after the construction of the first mechanical devices, machines that could act like humans, make decisions and talk began to play a major role in people’s lives. While the abilities of machines that look like humans and can do the work of humans both surprise and please people, the suspicion that one day machines that can think and decide will be able to dominate people has also come with it. Artificial intelligence, which emerged in the last stage of the Industrial Revolution process called Industry1 and in the Industry4 period, has been discussed a lot both technically and ethically, and has caused various doubts and fears.